Matematyka
MuszeSiku
2017-06-24 12:35:05
29. Zredukuj: [latex]10 sqrt{2}-6 sqrt{2};[/latex] [latex]5 sqrt{13}+ sqrt{13};[/latex] [latex]-4 sqrt{7}-9 sqrt{7};[/latex] [latex]- sqrt{101}+0,5 sqrt{101};[/latex] [latex]3 sqrt{c}-11 sqrt{c};[/latex] [latex]a sqrt{c}+b sqrt{c};[/latex] [latex]a sqrt{c}-b sqrt{c} .[/latex]
Odpowiedź
auk
2017-06-24 18:13:17

10 /2-6 /2=4 /2 5 /13+/13=6 /13 -4 /7-9 /7=-13 /7 -/101+0,5 /101=-0,5 /101 3 /c-11 /c=-8 /c a /c+b /c=(a+b) /c a /c-b /c=(a-b) /c / - ozn. pierwiastek

bolis
2017-06-24 18:14:32

[latex]10sqrt2-6sqrt2=(10-6)cdotsqrt2=4sqrt2\5sqrt{13}+sqrt{13}=5sqrt{13}+1sqrt{13}=(5+1)cdotsqrt{13}=6sqrt{13}\-4sqrt7-9sqrt7=(-4-9)cdotsqrt7=-13sqrt7\-sqrt{101}+0,5sqrt{101}=-1sqrt{101}+0,5sqrt{101}=(-1+0,5)cdotsqrt{101}=\=-0,5sqrt{101}\3sqrt{c}-11sqrt{c}=(3-11)cdotsqrt{c}=-8sqrt{c}\asqrt{c}+bsqrt{c}=(a+b)cdotsqrt{c}\asqrt{c}-bsqrt{c}=(a-b)cdotsqrt{c}[/latex]

Dodaj swoją odpowiedź